(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the self-efficacy and the relationship between self-efficacy and academic outcomes of medical students at Dai Nam University in 2024. Research subjects and methods: A cross-sectional descriptive study surveying 274 medical students at Dai Nam University in 2024 via Google form. Results: The average self-efficacy score was 27.4±6.8 (out of 40 points). The highest percentage of agreement was recorded with the opinion that students “expect to study well”, accounting for 38.7%, followed by “Confident that they can understand the basic concepts taught in the program”. curriculum” is 38.3%. The highest rate of Strongly Disagree and Disagree is for students who are “confident that they can understand the most complex material presented by the instructor”, 5.8% and 13.5%, respectively. The research results did not show that there was a statistically significant difference in self-efficacy scores between groups of students with different first-semester learning rankings and having to retake the exam during the semester. I, or have to relearn the situation up to the time of the survey (p>0.05). Conclusion: The self-efficacy of medical students at Dai Nam University was at an average level. The study also did not find a relationship between self-efficacy beliefs and academic performance of medical students.